A method for preparing a water-based tape-casting green body

By using specific proportions of silicon wafer powder and additives in the preparation of water-based cast green bodies, and using ball milling, ultrasonic homogenization and vacuum defoaming, wetting and degassing in water-based cast green bodies is solved. Problem, high-quality and environmentally friendly water-based cast green body preparation has been achieved.

CN118955137BActive Publication Date: 2025-02-11江苏富乐华功率半导体研究院有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411036876.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-02-11
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

In the existing water-based casting green body technology, the surface tension of water is high, making it difficult to effectively wet the ceramic powder, and it is difficult to remove the air, and bubbles seriously affect the quality of the blank.

Method used

Water using 30-50% silicon wafer powder, 1-2.5% dispersant, 5-10% binder, 1-5% plasticizer, 1-3% defoaming agent, 5-10% sintering additive The preparation method of base cast green body is improved by ball milling, ultrasonic homogenization, vacuum defoaming and other processes to improve dispersion and adhesion and reduce bubbles.

Benefits of technology

It realizes high-quality preparation of water-based cast green body, reduces bubble generation, improves the mechanical properties and yield of the blank, and has environmentally friendly processes and low cost.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of water-based tape-casting green body, and specifically discloses a preparation method of a water-based tape-casting green body, which comprises the following steps: S1: adding a dispersant into deionized water, homogenizing and obtaining a dispersion; S2: adding a sintering aid and silicon chip powder into the dispersion, and performing a ball milling and mixing at a speed of 150-250 r / min for 0.5-1 hour; during the ball milling, adding polydimethylsiloxane in batches every 10-20 minutes to obtain a mixture A; S3: adding a binder, a plasticizer and n-butanol into the mixture A, and performing a secondary ball milling and mixing at 150-250 r / min for 5-6 hours to obtain a mixture B; S4: filtering, high vacuum degassing, ultrasonic homogenizing, low vacuum degassing and standing for 20-30 minutes on the mixture B in sequence to obtain a slurry; S5: placing the slurry in a tape-casting machine, heating and drying to obtain a water-based tape-casting green body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water-based tape-casting green compacts, in particular to a method for preparing a water-based tape-casting green compact. Background Art

[0002] Tape casting is an important molding method for preparing large-area, thin and flat ceramic materials. It is also called tape casting and scraper method. It usually refers to the process of casting a viscous slurry on a film tape under constant pressure through the gap between the slurry scraper and the film tape coated with silicone and running at a certain speed. After drying and trimming, the cast film is separated from the film tape (or not separated) to obtain a cast film. Common types of ceramic substrates include aluminum oxide, aluminum nitride, silicon nitride, silicon carbide, etc. At present, silicon nitride green body tape casting mainly includes silicon wafer tape casting and silicon nitride powder tape casting. Compared with silicon nitride powder tape casting, silicon wafer tape casting consumes less energy in the preparation of silicon nitride powder, the price of silicon powder raw materials is cheap, high-purity silicon powder is relatively easy to obtain, and the oxygen content of silicon powder is much lower than that of silicon nitride powder, which is more conducive to sintering the green body to prepare high thermal conductivity silicon nitride ceramic sheets.

[0003] In this field, the most commonly used solvents for ceramic slurry tape casting are water and organic solvents. The advantages of the water-based system are safe use, environmental protection, and low cost; however, water has a large surface tension, making it difficult to effectively wet the ceramic powder, evaporating slowly and taking a long time to dry. The water-based system slurry is difficult to degas, and bubbles will seriously affect the quality of the green body. The organic system is more stable than the water-based system, with fewer and easier to remove bubbles, and the organic solvent is volatile and dries faster. However, the organic system has greater environmental problems and safety hazards; and there are problems such as poor dispersibility of components such as powders and sintering aids in the slurry and binder performance, which affect the quality of the water-based tape-cast green body.

[0004] In summary, it is of great significance to develop a water-based tape-casting green body with good dispersibility and adhesion. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a water-based tape-casting green body to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for preparing a water-based tape-casting green body. The raw materials of the water-based tape-casting green body include the following components: by mass, 30-50% silicon chip powder, 1-2.5% dispersant, 5-10% binder, 1-5% plasticizer, 1-3% defoamer, 5-10% sintering aid, and the rest is deionized water; the defoamer includes polydimethylsiloxane and n-butanol.

[0008] The more optimized method for preparing a water-based tape-cast green body comprises the following steps:

[0009] S1: adding the dispersant into deionized water and homogenizing it to obtain a dispersion;

[0010] S2: Add sintering aid and silicon wafer powder to the dispersion, and mix them by ball milling at a speed of 150 to 250 r / min for 0.5 to 1 hour; during the ball milling process, add polydimethylsiloxane in batches every 10 to 20 minutes to obtain a mixture A;

[0011] S3: Add a binder, a plasticizer, and n-butanol to the mixture A, and perform secondary ball milling at 150-250 r / min for 5-6 hours to obtain a mixture B;

[0012] S4: The mixture B is filtered, degassed under high vacuum, homogenized under ultrasonication, degassed under low vacuum, and allowed to stand for 20 to 30 minutes to obtain a slurry;

[0013] S5: placing the slurry in a tape casting machine, heating and drying, and obtaining a water-based tape casting green body.

[0014] Preferably, the mass ratio of n-butanol to polydimethylsiloxane is (1-2):1.

[0015] More optimally, the process conditions for high vacuum degassing are: vacuum degree ≥-0.09MPa, and the vacuum degassing time is 30 to 40 minutes; the process conditions for ultrasonic homogenization are: ultrasonic power is 50 to 100W, and the ultrasonic time is 10 to 20 minutes; the process conditions for low vacuum degassing are: vacuum degree is -0.04MPa to -0.05MPa, and the vacuum degassing time is 30 to 60 minutes; the process conditions for heating and drying are: initial temperature is 45 to 55°C, insulation temperature is 60 to 70°C, insulation time is 1 to 2 hours, end temperature is 85 to 95°C, and insulation is 5 to 8 minutes every 5°C during the heating stage.

[0016] More optimally, the silicon wafer powder is single crystal silicon powder with a purity greater than 99.99%, the impurity contents of Fe, Al and Ca are all less than 200 ppm, and the particle size D50 of the silicon wafer powder is 2 to 10 um; the plasticizer is polyethylene glycol; and the viscosity control range of the slurry is 4000 to 7000 cps.

[0017] Preferably, the dispersant includes one or more of acrylic polymers, ester polymers, olefin polymers, and ether polymers; and the binder includes polyvinyl alcohol.

[0018] More optimally, the binder is modified polyvinyl alcohol; its preparation method is: (1) 2,3,5,6-tetraaminopyridine hydrochloride and 4,4'-methylenebis(phenyl isocyanate) are uniformly mixed, and reacted at 70-80°C for 20-22 hours under nitrogen protection to obtain an intermediate; (2) polyvinyl alcohol and hydroxyethyl methacrylate are added to chloroform and uniformly mixed, and the intermediate and dibutyltin dilaurate are added; reacted at 70-80°C for 10-18 hours, silicon dioxide is added and stirred for 1-2 hours, washed and dried to obtain modified polyvinyl alcohol.

[0019] More optimally, the mass ratio of the 2,3,5,6-tetraaminopyridine hydrochloride to 4,4'-methylenebis(phenyl isocyanate) is 1:(6-8); the raw materials of the modified polyvinyl alcohol include the following components: by weight, 6-7.5 parts of polyvinyl alcohol, 1-2.2 parts of hydroxyethyl methacrylate, 2-3.2 parts of intermediates, 0.01-0.022 parts of dibutyltin dilaurate, and 4-5 parts of silicon dioxide.

[0020] More preferably, the dispersant is a polymethyl acrylate complex, and its preparation method is as follows: (1) placing 1,3-divinyl-1,1,3,3-tetramethyldisilazane, AIBN, and bis(3-mercaptopropionic acid)ethylene glycol in tetrahydrofuran, mixing them evenly, irradiating them under ultraviolet light of 350-365 nm and 80-100 W for 1-2 hours, and purifying them to obtain an intermediate product; (2) adding polymethyl acrylate to the intermediate product, mixing them evenly, and reacting them at 115-120° C. for 18-22 hours to obtain a polymethyl acrylate complex.

[0021] More optimally, the raw materials of the intermediate product include the following components: by weight, 1 to 1.5 parts of 1,3-divinyl-1,1,3,3-tetramethyldisilazane, 0.001 to 0.002 parts of AIBN, 2 to 3 parts of bis(3-mercaptopropionic acid)ethylene glycol, and 50 to 55 parts of tetrahydrofuran; the mass ratio of the intermediate product to polymethyl acrylate is 1:(2 to 3.5).

[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) the water-based silicon powder casting system used in the present invention is both safe and environmentally friendly, and has low cost; (2) the mixed use of a defoaming agent for glue and a defoaming agent for water greatly reduces the generation of bubbles and improves the quality of the cast green body; (3) the mixed use of high and low vacuum degassing and ultrasonic degassing effectively removes bubbles in the slurry; (4) water vapor is introduced during the heat preservation stage to increase the vapor pressure, reduce the volatilization rate of the surface solvent, and reduce the risk of cracking; (5) the use of a variety of organic additives can reduce the difficulty of casting and improve the quality of the green body.

[0023] The present invention reacts silazane with bis(3-mercaptopropionic acid)ethylene glycol through a click chemistry reaction to obtain a silazane intermediate product containing a mercapto group; and then compounds the intermediate product with polymethyl acrylate to obtain a polymethyl acrylate dispersant containing a mercapto group and silazane.

[0024] Among them, the introduction of mercapto groups can increase the bonding points between the dispersant and the surface of silicon powder and metal oxides, and improve the flow properties of the dispersant in the fluid, so that it can better wrap and disperse the particles; silazane is an organic compound containing silicon and nitrogen elements, with good high temperature resistance and chemical stability; it improves the dispersibility of the dispersant with particles such as silicon powder, yttrium oxide, magnesium oxide and zirconium oxide in the water-based tape casting slurry, thereby improving the mechanical properties of the green body.

[0025] In order to firmly combine the components in the slurry, thereby improving the bonding strength of the water-based tape-cast green body; the present invention reacts the amino group on 2,3,5,6-tetraaminopyridine hydrochloride with the cyano group on 4,4'-methylenebis(phenyl isocyanate) to obtain an intermediate; the cyano group on the intermediate reacts with the hydroxyl group on polyvinyl alcohol to obtain a binder containing multiple NH covalent bonds, thereby forming multiple hydrogen bond structures on the polyvinyl alcohol molecules, which is beneficial to the water-based tape-cast green body to form a strong hydrogen bond force with other components during the production process, firmly bond various materials together, form a stable structure, and thus enhance adhesion and adhesion. DETAILED DESCRIPTION

[0026] The following is a preferred implementation of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principle of the embodiment of the present invention are within the scope of protection of the present invention.

[0027] In the following specific embodiments, parts are by weight. In this embodiment, it should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions, and exemplary examples include: CAS No. 38926-45-3 of 2,3,5,6-tetraaminopyridine hydrochloride, CAS No. 101-68-8 of 4,4'-methylenebis(phenyl isocyanate), model No. S30196 of polyvinyl alcohol, CAS No. 868-77-9 of hydroxyethyl methacrylate, CAS No. 77-58-7 of dibutyltin dilaurate, and CAS No. 77-58-7 of di( The CAS number of ethylene glycol (3-mercaptopropionic acid) is 22504-50-3, the CAS number of 1,3-divinyl-1,1,3,3-tetramethyldisilazane is 7691-02-3, the CAS number of polymethyl acrylate is 9003-21-8, the molecular weight of plasticizer polyethylene glycol is 400, the CAS number of n-butanol is 71-36-3, the CAS number of polydimethylsiloxane is 9016-00-6, the product number of zirconium oxide is DS140, the product number of yttrium oxide is S24438, and the product number of magnesium oxide is S27399.

[0028] The preparation method of modified polyvinyl alcohol is as follows: (1) 2,3,5,6-tetraaminopyridine hydrochloride and 4,4'-methylenebis(phenyl isocyanate) are uniformly mixed at a mass ratio of 1:6.5, and reacted at 75°C for 20 hours under nitrogen protection to obtain an intermediate; (2) 7 parts of polyvinyl alcohol and 1.8 parts of hydroxyethyl methacrylate are added to 100 parts of chloroform and uniformly mixed, and 2.5 parts of the intermediate and 0.01 parts of dibutyltin dilaurate are added; the mixture is reacted at 75°C for 16 hours, 5 parts of silicon dioxide are added, the mixture is stirred for another hour, washed, and dried to obtain modified polyvinyl alcohol.

[0029] The preparation method of the polymethyl acrylate complex is as follows: (1) placing 1.5 parts of 1,3-divinyl-1,1,3,3-tetramethyldisilazane, 0.002 parts of AIBN, and 3 parts of bis(3-mercaptopropionic acid)ethylene glycol in 50 parts of tetrahydrofuran, uniformly mixing, irradiating under ultraviolet light of 365 nm and 100 W for 2 hours, and purifying to obtain an intermediate product; (2) adding polymethyl acrylate to the intermediate product, uniformly mixing, and reacting it at 120° C. for 22 hours to obtain a polymethyl acrylate complex; the mass ratio of the intermediate product to the polymethyl acrylate is 1:2.7.

[0030] Embodiment 1:

[0031] Raw material preparation: The raw materials of the water-based tape casting green body are weighed according to the following mass fractions: 34% silicon wafer powder, 1% polymethyl acrylate (dispersant), 6% polyvinyl alcohol (binder), 2% plasticizer, 2% defoamer, 5% sintering aid, and the rest is deionized water; wherein the raw materials of the sintering aid include the following components by mass fraction: 3% yttrium oxide, 1% magnesium oxide, and 1% zirconium oxide; the raw materials of the defoamer include the following components by mass fraction: 1% n-butanol and 1% polydimethylsiloxane;

[0032] S1: Ultrasonic pre-dissolution: add the dispersant into deionized water, use an ultrasonic homogenizer to evenly dissolve the dispersant in the solvent, the ultrasonic power is 200W, the ultrasonic time is 3 minutes, and a dispersion is obtained;

[0033] S2: primary ball milling: sintering aid, silicon powder and dispersion were mixed and added into a ball mill, and ball milled for 0.5 hours using a planetary ball mill at a speed of 200 r / min. Polydimethylsiloxane was added into the ball mill three times at intervals of 10 minutes to obtain a mixture A;

[0034] S3: Secondary ball milling: Add the binder, plasticizer and n-butanol to the mixture A, and use a planetary ball mill to mill for 6 hours at a speed of 200 r / min to obtain a mixture B;

[0035] S4: Degassing: Filter the mixture B with a 200-mesh sieve, place the filtered mixture B in a vacuum degassing machine, adjust the vacuum degree to above -0.09MPa, and perform vacuum degassing for 30 minutes. Place the mixture B after high vacuum degassing in an ultrasonic homogenizer, and perform low-power (75W) ultrasonic homogenization for 10 minutes. Place the mixture B after ultrasonic homogenization in a vacuum degassing machine for low vacuum degassing (vacuum degree -0.04MPa) for 40 minutes. Let the mixture B after low vacuum degassing stand for 30 minutes to obtain a slurry. The viscosity of the slurry is controlled at 6000cps.

[0036] S5: Casting and drying: adjust the knife height and speed of the casting machine, pump the slurry into the casting machine, and after the casting is completed, heat and dry to obtain a water-based cast green body; the initial temperature is 45°C, the insulation temperature is 60°C (insulation for 1.5 hours, during the insulation process, it is necessary to introduce a proper amount of water vapor to increase the vapor pressure, reduce the evaporation rate of the surface solvent, and reduce the risk of cracking), and the end temperature is 95°C (the secondary heating stage requires insulation for 5 minutes every 5°C).

[0037] Embodiment 2:

[0038] Raw material preparation: The raw materials of the water-based tape casting green body are weighed according to the following mass fractions: 31% silicon wafer powder, 1.5% polymethyl acrylate (dispersant), 6% polyvinyl alcohol (binder), 2% plasticizer, 2% defoamer, 7.5% sintering aid, and the rest is deionized water; wherein the raw materials of the sintering aid include the following components: by mass fraction, 4% yttrium oxide, 2.5% magnesium oxide, and 1% zirconium oxide; the raw materials of the defoamer include the following components: by mass fraction, 1% n-butanol and 1% polydimethylsiloxane;

[0039] S1: Ultrasonic pre-dissolution: add the dispersant into deionized water, and use an ultrasonic homogenizer to uniformly dissolve the dispersant in the solvent, with an ultrasonic power of 250 W and an ultrasonic time of 4 minutes to obtain a dispersion;

[0040] S2: primary ball milling: sintering aid, silicon powder and dispersion were mixed and added into a ball mill, and ball milled for 1 hour using a planetary ball mill at a speed of 180 r / min. Polydimethylsiloxane was added into the ball mill three times at intervals of 20 minutes to obtain a mixture A;

[0041] S3: secondary ball milling: adding a binder, a plasticizer and n-butanol to the mixture A, and ball milling for 6 hours at a rotation speed of 200 r / min using a planetary ball mill to obtain a mixture B;

[0042] S4: Degassing: Filter the mixture B with a 200-mesh sieve, place the filtered mixture B in a vacuum degassing machine, adjust the vacuum degree to above -0.09MPa, and perform vacuum degassing for 40 minutes. Place the mixture B after high vacuum degassing in an ultrasonic homogenizer, and perform low-power (100W) ultrasonic homogenization for 15 minutes. Place the mixture B after ultrasonic homogenization in a vacuum degassing machine for low vacuum degassing (vacuum degree -0.05MPa) for 40 minutes. Let the mixture B after low vacuum degassing stand for 30 minutes to obtain a slurry. The viscosity of the slurry is controlled at 5500cps.

[0043] S5: Casting and drying: adjust the knife height and speed of the casting machine, pump the slurry into the casting machine, and after the casting is completed, heat and dry to obtain a water-based cast green body; the initial temperature is 50°C, the insulation temperature is 65°C (insulation for 2 hours, during the insulation process, it is necessary to introduce a proper amount of water vapor to increase the vapor pressure, reduce the volatilization rate of the surface solvent, and reduce the risk of cracking), and the end temperature is 95°C (the secondary heating stage needs to be kept warm for 5 minutes every 5°C).

[0044] Example 3 is based on Example 1, and the slurry viscosity is controlled at 7000cps;

[0045] S1: Ultrasonic pre-dissolution: add the dispersant into deionized water, use an ultrasonic homogenizer to evenly dissolve the dispersant in the solvent, the ultrasonic power is 200W, the ultrasonic time is 3 minutes, and a dispersion is obtained;

[0046] S2: primary ball milling: sintering aid, silicon powder and dispersion were mixed and added into a ball mill, and ball milled for 0.5 hours using a planetary ball mill at a speed of 200 r / min. Polydimethylsiloxane was added into the ball mill three times at intervals of 10 minutes to obtain a mixture A;

[0047] S3: secondary ball milling: adding a binder, a plasticizer and n-butanol to the mixture A, and ball milling for 6 hours at a rotation speed of 200 r / min using a planetary ball mill to obtain a mixture B;

[0048] S4: Degassing: Filter the mixture B with a 200-mesh sieve, place the filtered mixture B in a vacuum degassing machine, adjust the vacuum degree to above -0.09MPa, and perform vacuum degassing for 30 minutes. Place the mixture B after high vacuum degassing in an ultrasonic homogenizer, and perform low-power (75W) ultrasonic homogenization for 10 minutes. Place the ultrasonically homogenized mixture B in a vacuum degassing machine for low vacuum degassing (vacuum degree -0.04MPa) for 40 minutes. Let the mixture B after low vacuum degassing stand for 30 minutes to obtain a slurry. The viscosity of the slurry is controlled at 7000cps.

[0049] S5: Casting and drying: adjust the knife height and speed of the casting machine, pump the slurry into the casting machine, and after the casting is completed, heat and dry to obtain a water-based cast green body; the initial temperature is 45°C, the insulation temperature is 60°C (insulation for 1.5 hours, during the insulation process, it is necessary to introduce a proper amount of water vapor to increase the vapor pressure, reduce the evaporation rate of the surface solvent, and reduce the risk of cracking), and the end temperature is 95°C (the secondary heating stage requires insulation for 5 minutes every 5°C).

[0050] Example 4 Based on Example 1, polyvinyl alcohol (binder) and polymethyl acrylate (dispersant) are optimized;

[0051] S1: Ultrasonic pre-dissolution: add the dispersant into deionized water, use an ultrasonic homogenizer to evenly dissolve the dispersant in the solvent, the ultrasonic power is 200W, the ultrasonic time is 3 minutes, and a dispersion is obtained;

[0052] S2: primary ball milling: sintering aid, silicon powder and dispersion were mixed and added into a ball mill, and ball milled for 0.5 hours using a planetary ball mill at a speed of 200 r / min. Polydimethylsiloxane was added into the ball mill three times at intervals of 10 minutes to obtain a mixture A;

[0053] S3: secondary ball milling: adding a binder, a plasticizer and n-butanol to the mixture A, and ball milling for 6 hours at a rotation speed of 200 r / min using a planetary ball mill to obtain a mixture B;

[0054] S4: Degassing: Filter the mixture B with a 200-mesh sieve, place the filtered mixture B in a vacuum degassing machine, adjust the vacuum degree to above -0.09MPa, and perform vacuum degassing for 30 minutes. Place the mixture B after high vacuum degassing in an ultrasonic homogenizer, and perform low-power (75W) ultrasonic homogenization for 10 minutes. Place the mixture B after ultrasonic homogenization in a vacuum degassing machine for low vacuum degassing (vacuum degree -0.04MPa) for 40 minutes. Let the mixture B after low vacuum degassing stand for 30 minutes to obtain a slurry. The viscosity of the slurry is controlled at 6000cps.

[0055] S5: Casting and drying: adjust the knife height and speed of the casting machine, pump the slurry into the casting machine, and after the casting is completed, heat and dry to obtain a water-based cast green body; the initial temperature is 45°C, the insulation temperature is 60°C (insulation for 1.5 hours, during the insulation process, it is necessary to introduce a proper amount of water vapor to increase the vapor pressure, reduce the evaporation rate of the surface solvent, and reduce the risk of cracking), and the end temperature is 95°C (the secondary heating stage requires insulation for 5 minutes every 5°C).

[0056] Comparative Example 1 is based on Example 4, but the binder polyvinyl alcohol is not modified;

[0057] S1: Ultrasonic pre-dissolution: add the dispersant into deionized water, use an ultrasonic homogenizer to evenly dissolve the dispersant in the solvent, the ultrasonic power is 200W, the ultrasonic time is 3 minutes, and a dispersion is obtained;

[0058] S2: primary ball milling: sintering aid, silicon powder and dispersion were mixed and added into a ball mill, and ball milled for 0.5 hours using a planetary ball mill at a speed of 200 r / min. Polydimethylsiloxane was added into the ball mill three times at intervals of 10 minutes to obtain a mixture A;

[0059] S3: Secondary ball milling: Add the binder, plasticizer and n-butanol to the mixture A, and use a planetary ball mill to mill for 6 hours at a speed of 200 r / min to obtain a mixture B;

[0060] S4: Degassing: Filter the mixture B with a 200-mesh sieve, place the filtered mixture B in a vacuum degassing machine, adjust the vacuum degree to above -0.09MPa, and perform vacuum degassing for 30 minutes. Place the mixture B after high vacuum degassing in an ultrasonic homogenizer, and perform low-power (75W) ultrasonic homogenization for 10 minutes. Place the mixture B after ultrasonic homogenization in a vacuum degassing machine for low vacuum degassing (vacuum degree -0.04MPa) for 40 minutes. Let the mixture B after low vacuum degassing stand for 30 minutes to obtain a slurry. The viscosity of the slurry is controlled at 6000cps.

[0061] S5: Casting and drying: adjust the knife height and speed of the casting machine, pump the slurry into the casting machine, and after the casting is completed, heat and dry to obtain a water-based cast green body; the initial temperature is 45°C, the insulation temperature is 60°C (insulation for 1.5 hours, during the insulation process, it is necessary to introduce a proper amount of water vapor to increase the vapor pressure, reduce the evaporation rate of the surface solvent, and reduce the risk of cracking), and the end temperature is 95°C (the secondary heating stage requires insulation for 5 minutes every 5°C).

[0062] Comparative Example 2 is based on Example 4, except that n-butanol and ultrasonic defoaming are introduced alone;

[0063] S1: Ultrasonic pre-dissolution: add the dispersant into deionized water, use an ultrasonic homogenizer to evenly dissolve the dispersant in the solvent, the ultrasonic power is 200W, the ultrasonic time is 3 minutes, and a dispersion is obtained;

[0064] S2: primary ball milling: 5% by mass of sintering aid, 34% by mass of silicon powder and dispersion were mixed and added into a ball milling jar, and ball milled for 0.5 hours at a speed of 200 r / min using a planetary ball mill to obtain a mixture A;

[0065] S3: secondary ball milling: adding a binder, a plasticizer and n-butanol to the mixture A, and ball milling for 6 hours at a rotation speed of 200 r / min using a planetary ball mill to obtain a mixture B;

[0066] S4: Degassing: Filter the mixture B using a 200-mesh sieve, place the filtered mixture B in an ultrasonic homogenizer, and homogenize it with low power (75W) ultrasound for 70 minutes, and let the ultrasonically homogenized mixture B stand for 30 minutes to obtain a slurry; the viscosity of the slurry is controlled at 6000cps;

[0067] S5: Casting and drying: adjust the knife height and speed of the casting machine, pump the slurry into the casting machine, and after the casting is completed, heat and dry to obtain a water-based cast green body; the initial temperature is 45°C, the insulation temperature is 60°C (insulation for 1.5 hours, during the insulation process, it is necessary to introduce a proper amount of water vapor to increase the vapor pressure, reduce the evaporation rate of the surface solvent, and reduce the risk of cracking), and the end temperature is 95°C (the secondary heating stage requires insulation for 5 minutes every 5°C).

[0068] Test experiment 1: 100 water-based tape-cast green sheets of Examples 1 to 4 and Comparative Examples 1 to 2 were prepared, and the yield of Examples 1 to 3 was calculated; 6 intact green sheets of Examples 1 to 4 and Comparative Examples 1 to 2 were taken respectively, and their tensile strength was tested.

[0069] Tensile strength(MPa) Yield rate (%) Example 1 2.92 95 Example 2 2.67 87 Example 3 2.86 92 Example 4 3.27 98 Comparative Example 1 3.12 96 Comparative Example 2 3.04 85

[0070] Table 1

[0071] Conclusion: It can be seen from Examples 1 to 3 in Table 1 that when the slurry viscosity is 6000cps, the yield is better. Example 4 is based on Example 1, and polyvinyl alcohol (binder) and polymethyl acrylate (dispersant) are optimized to improve the yield and tensile strength of Example 4. Comparative Example 1 is based on Example 4, and the binder polyvinyl alcohol is not modified, resulting in a decrease in the hydrogen bonding force between the binder and each component, thereby reducing the tensile strength and yield of the water-based tape-cast green body. Comparative Example 2 is based on Example 4, and only n-butanol and ultrasonic defoaming are introduced, thereby reducing the tensile strength and yield; because the mixed use of glue defoaming agent and water defoaming agent, as well as the mixed use of high and low vacuum degassing and ultrasonic defoaming, can greatly reduce the generation of bubbles, thereby improving the quality of the water-based tape-cast green body.

[0072] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.

Claims

1. A method for preparing a water-based tape-cast green body, characterized in that: The steps include: S1: adding the dispersant into deionized water and homogenizing it to obtain a dispersion; S2: Add sintering aid and silicon wafer powder to the dispersion, and mix them by ball milling at a speed of 150 to 250 r / min for 0.5 to 1 hour; during the ball milling process, add polydimethylsiloxane in batches every 10 to 20 minutes to obtain a mixture A; S3: Add a binder, a plasticizer, and n-butanol to the mixture A, and perform secondary ball milling at 150-250 r / min for 5-6 hours to obtain a mixture B; S4: The mixture B is filtered, degassed under high vacuum, homogenized under ultrasonication, degassed under low vacuum, and allowed to stand for 20 to 30 minutes to obtain a slurry; S5: placing the slurry in a tape casting machine, heating and drying, and obtaining a water-based tape casting green body; The raw materials of the water-based tape casting green body include the following components: by weight, 30-50% silicon wafer powder, 1-2.5% dispersant, 5-10% binder, 1-5% plasticizer, 1-3% defoamer, 5-10% sintering aid, and the rest is deionized water; the defoamer includes polydimethylsiloxane and n-butanol; The binder is modified polyvinyl alcohol; the preparation method thereof is as follows: (1) uniformly mixing 2,3,5,6-tetraaminopyridine hydrochloride and 4,4'-methylenebis(phenyl isocyanate), reacting at 70-80°C for 20-22 hours under nitrogen protection to obtain an intermediate; (2) adding polyvinyl alcohol and hydroxyethyl methacrylate to chloroform and uniformly mixing, adding the intermediate and dibutyltin dilaurate; reacting at 70-80°C for 10-18 hours, adding silicon dioxide and continuing stirring for 1-2 hours, washing and drying to obtain modified polyvinyl alcohol; The dispersant is a polymethyl acrylate complex, and the preparation method thereof is as follows: (1) placing 1,3-divinyl-1,1,3,3-tetramethyldisilazane, AIBN, and bis(3-mercaptopropionic acid)ethylene glycol in tetrahydrofuran, uniformly mixing, irradiating under ultraviolet light of 350-365 nm and 80-100 W for 1-2 hours, purifying, and obtaining an intermediate product; (2) adding polymethyl acrylate to the intermediate product, uniformly mixing, and purifying the intermediate product at 11 The reaction is carried out at 5 to 120° C. for 18 to 22 hours to obtain a polymethyl acrylate complex; the raw materials of the intermediate product include the following components: by weight, 1 to 1.5 parts of 1,3-divinyl-1,1,3,3-tetramethyldisilazane, 0.001 to 0.002 parts of AIBN, 2 to 3 parts of bis(3-mercaptopropionic acid)ethylene glycol, and 50 to 55 parts of tetrahydrofuran; the mass ratio of the intermediate product to polymethyl acrylate is 1:(2 to 3.5).

2. The method for preparing a water-based tape-cast green body according to claim 1, characterized in that: The mass ratio of n-butanol to polydimethylsiloxane is (1-2):

1.

3. The method for preparing a water-based tape-casting green body according to claim 1, characterized in that: The process conditions of high vacuum degassing are: vacuum degree ≥-0.09MPa, and vacuum degassing time is 30 to 40 minutes; the process conditions of ultrasonic homogenization are: ultrasonic power is 50 to 100W, and ultrasonic time is 10 to 20 minutes; the process conditions of low vacuum degassing are: vacuum degree is -0.04MPa to -0.05MPa, and vacuum degassing time is 30 to 60 minutes; the process conditions of heating and drying are: initial temperature is 45 to 55°C, insulation temperature is 60 to 70°C, insulation time is 1 to 2 hours, end temperature is 85 to 95°C, and insulation is 5 to 8 minutes every 5°C during the heating stage.

4. The method for preparing a water-based tape-casting green body according to claim 1, characterized in that: The silicon chip powder is single crystal silicon powder with a purity greater than 99.99%, Fe, Al and Ca impurity contents less than 200 ppm, and a particle size D50 of 2 to 10 um; the plasticizer is polyethylene glycol; and the viscosity control range of the slurry is 4000 to 7000 cps.

5. The method for preparing a water-based tape-casting green body according to claim 1, characterized in that: The mass ratio of 2,3,5,6-tetraaminopyridine hydrochloride to 4,4'-methylenebis(phenyl isocyanate) is 1:(6-8); the raw materials of the modified polyvinyl alcohol include the following components: by weight, 6-7.5 parts of polyvinyl alcohol, 1-2.2 parts of hydroxyethyl methacrylate, 2-3.2 parts of intermediates, 0.01-0.022 parts of dibutyltin dilaurate, and 4-5 parts of silicon dioxide.

6. A water-based tape-casting green body prepared according to the method for preparing a water-based tape-casting green body according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Composite ceramic precursors and layers

    EP1156024A1

  • Silicon nitride ceramic having high heat conduction and its production

    JP1997165265A